Genetic and Epigenetic Therapies for β-Thalassaemia by Altering the Expression of α-Globin Gene - Mettananda, Sachith (Frontiers in Genome Editing, 2021)
β-Thalassaemia is caused by over 300 mutations in and around the β-globin gene that lead to impaired synthesis of β-globin. The expression of α-globin continues normally, resulting in an excess of α-globin chains within red blood cells and their precursors. These unpaired α-globin chains form unstable α-hemichromes that trigger cascades of events to generate reactive oxygen species, leading to ineffective erythropoiesis and haemolysis in patients with β-thalassaemia. The clinical genetic data reported over several decades have demonstrated how the coinheritance of α-thalassaemia ameliorates the disease phenotype of β-thalassaemia. Thus, it is evident that downregulation of the α-globin gene expression in patients with β-thalassaemia could ameliorate or even cure β-thalassaemia. Over the last few years, significant progress has been made in utilising this pathway to devise a cure for β-thalassaemia. Most research has been done to alter the epigenetic landscape of the α-globin locus or the well-characterised distant enhancers of α-globin. In vitro, pre-clinical studies on primary human erythroid cells have unveiled inhibition of histone lysine demethylation and histone deacetylation as potential targets to achieve selective downregulation of α-globin through epigenetic drug targeting. CRISPR based genome editing has been successfully used in vitro to mutate α-globin genes or enhancers of α-goblin to achieve clinically significant knockdowns of α-globin to the levels beneficial for patients with β-thalassaemia. This review summarises the current knowledge on the regulation of human α-globin genes and the clinical genetic data supporting the pathway of targeting α-globin as a treatment for β-thalassaemia. It also presents the progress of epigenetic drug, and genome editing approaches currently in development to treat β-thalassaemia.